Tradisi Shalawat Ngelik di Kampung Santri Mlangi, Sleman, DIY - Nur Rokhim (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2020)
The tradition of ngelik prayer is one of the traditions of the celebration of the birth of the Prophet Muhammad, in the Santri Village in Mlangi, Sleman, DIY. This tradition is carried out at the peak of the prophet's birthday celebration which is the 12th of Rabiu'ul Awal at Pathok Negoro Mosque in Mlangi. This research tries to reveal in detail the tradition and try to analyze why this tradition still exists today. This study uses two data collection techniques, namely literature and field studies. The approach used is a qualitative approach with an ethnographic model. This research reveals a brief history of Santri Mlangi Village formed by the initiative of KH. Nur Iman Mlangi, sibling of Sultan Hamengkubuwono I. This research also found that the tradition of ngelik prayer is a new culture as a result of a cross between Islamic and Javanese cultures. The celebration of the birthday of the Prophet Muhammad SAW, is an Islamic culture. While recitation of shalawat using Javanese-style notes is a Javanese tradition. This is inseparable from the influence of the existence of KH. Nur Iman Mlangi who is a royal descendant of the Yogyakarta Palace. This study also revealed that the existence of dozens of pesantren has a big role in maintaining the continuity of the tradition of ngelik prayer. Keywords: Shalawat Ngelik, Mlangi, Pathok Negoro Mosque